The Importance of House Pets in Emotional Development - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
Pets are useful to people in the psychological sense. Livestock, poultry and working animals can not be surrogates for pets. In the modern society pets are gaining more and more importance. In Turkey, too, pet-keeping is getting to be a widespread practice in recent times. Pets represent animal love and they especially contribute to children's healthy emotional development. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Pets; animal love; psychological support